Understanding HIV transmission and prevention among men who have sex with men in a sexual health clinic - Kumareswaran, Suriya; Sundram, Bala Murali (Intelektual Pustaka Media Utama, 2025)
This comprehensive study investigates the knowledge, attitudes, and practices (KAP) concerning human immunodeficiency virus (HIV) transmission and prevention among men who have sex with men (MSM) in a sexually transmitted infections (STI)-friendly clinic in Johor, Malaysia. Utilizing a cross-sectional design, the study analyses data from 421 MSM patients, emphasizing the critical role of sociodemographic factors in influencing HIV-related behaviors. The majority of participants, mostly with tertiary education, displayed a sound understanding of HIV, with 71% showing good knowledge on HIV prevention and transmission. However, there remain gaps in knowledge, particularly among those with lesser education, and in practices related to condom use and pre-exposure prophylaxis (PrEP). The study highlights a stark disparity in HIV-related attitudes and practices based on education level, employment status, and income. Notably, those with higher education and income levels demonstrate more responsible practices and better knowledge, underscoring the need for tailored educational programs. The findings call for comprehensive and targeted interventions, considering the diverse backgrounds of individuals, to effectively mitigate the risk of HIV infection. This research is vital in the absence of a definitive cure for HIV and acquired immune deficiency syndrome (AIDS), emphasizing preventive measures based on accurate information and positive attitudes towards the disease.